PENGUATAN IKLIM SEKOLAH DENGAN PELATIHAN PADA SISWA, GURU DAN ORANG TUA DALAM MENDAMPINGI PEMBELAJARAN ANAK SDN 10 PONDOK PINANG DI ERA DIGITAL - Yuliana Mukti Rahmawati; Anisa Rahmadani; Firman Mansir; Harmathilda Harmathilda; Yudi Ali Akbar; Bahrul Ulum (BESIRU : Jurnal Pengabdian Masyarakat, 2026)
The learning process in society 5.0 is facing real challenges with the rapid development of informations and technologies.This social services aim to facilitate the school’s environment from problems that happened from student’s maladaptive internet use. Achieving the optimum impact, this social service give the training to improve awereness related issued for teacher and parents. This social service also give training directly for student in the form of extending attention span, cognitive flexibility and regulated emotion. There’s knowlegdes improvement and better understanding from teacher and parents about their children or student used of internet proven by their knowlege about parental guidance application and how to use it for their children behavior using smartphone